2018
DOI: 10.3389/fvets.2018.00142
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight Impairs Acquisition of Spatial Memory Task in Pigs

Abstract: In commercial pig farming, an increasing number of low birth weight (LBW) piglets are born, due to selection for large litter sizes. While LBW piglets have a higher risk of pre-weaning mortality, a considerable number of these piglets survive to slaughter age. In humans, LBW is a risk factor for long-term cognitive impairments. In pigs, studies examining the post-weaning effects of LBW on cognition have reported contradictory results. Therefore, the current study aimed to assess the effects of LBW on cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
(127 reference statements)
2
8
0
Order By: Relevance
“…Perhaps the enriched housing conditions applied during our study also had such an ameliorating effect on the pigs’performance (Sneddon et al 2000; Grimberg-Henrici et al 2016), resulting in only a mild impairment compared to the NBW pigs. Similar mild effects have also been found for other cognitive domains in LBW pigs, such as spatial learning and memory (Gieling et al 2012; Radlowski et al 2014; Roelofs et al 2018; cf. Antonides et al 2015).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…Perhaps the enriched housing conditions applied during our study also had such an ameliorating effect on the pigs’performance (Sneddon et al 2000; Grimberg-Henrici et al 2016), resulting in only a mild impairment compared to the NBW pigs. Similar mild effects have also been found for other cognitive domains in LBW pigs, such as spatial learning and memory (Gieling et al 2012; Radlowski et al 2014; Roelofs et al 2018; cf. Antonides et al 2015).…”
Section: Discussionsupporting
confidence: 65%
“…Further indication that group composition may influence emotional state in pigs comes from a finding of impaired behavioral flexibility in male pigs when housed in a single-sex group (Roelofs et al 2017b). When this study was repeated with mixed-sex housing, no difference in behavioral flexibility between females and males was found (Roelofs et al 2018). The composite effects of various elements of pigs’ social environment are likely complex, as is also indicated by our finding of male pigs responding more pessimistically than females.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This could have been an important bias in case sex influences cortisol concentration in horsehair, independent of the degree of stress. Literature on this topic is scarce, but in general, research agrees on the lack of sex differences in hair cortisol, particularly in other species such as cows and piglets [ 31 ], bears [ 32 ], lynx [ 33 ], pigs [ 34 ], and dogs [ 35 ]. Few studies have been carried out on horses; in one case, higher hair concentrations were found in healthy newborn foals compared to healthy adult horses [ 36 ].…”
Section: Discussionmentioning
confidence: 99%